Gerusan Lokal Di Sekitar Pilar Jembatan Bentuk Oblong Dengan Material Dasar Sungai Kampar - Imam Syafni L; Mudjiatko Mudjiatko; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Local scours that occur continuously will cause damage to the pillars of the bridge that can endanger the stability of the bridge structure. Laboratory model has been developed to identify the phenomena of local scour on the oblong pillar with and without pillar protector. Kampar sand with grain size d35 = 0,285 mm, d50 = 0,330 mm and d65 = 0,380 mm and Gs = 2,63 is used in the bed of flume model. Three variations of  flow used in this research is classified on the type of subcritical flow with Froude number ranged from 0,46354 – 0,76903. Reynolds number in Fr1 scored 1658,416 (transitional flow), Fr2 scored 3081,683 and Fr3 scored 4381,188 then included in the turbulent flow. The results of the data analysis showed base granular moves in each test Froude value shown in the diagram Shields. Hjulstorm graphic also shows that the granules of gradation used in this research in moving zone. Hydrodynamic flow on the pillars of the downflow lead and create horsehoe vortex at the base of the pillar which eroded material around the pillar . Scour that occurs started having equilibrium at minute 75 . The maximum ratio of scour depth (ds/b)  is 0,44 which occurs in Q3PL .Pillar protector of curtain type can reduce scour depths up to 28,57%. Sediment transport analysis results proved that the higher the Froude number is used, the bigger the granules are transported.  Key Word : local scouring, laboratory model, oblong pillar, hydrodynamic flow,  depth ratio